Dual negative roles of C/EBPα in the expansion and pro-tumor functions of MDSCs. Issue 1 (December 2017) - Mackert, John; Qu, Peng; Min, Yongfen; Johnson, Peter F.; Yang, Li; Lin, P.
Abstract Myeloid-derived suppressor cells (MDSCs) are greatly expanded in cancer patients and tumor-bearing mice. They infiltrate into tumors and modulate the tumor microenvironment. In an effort to identify molecular mediators responsible for expansion and the tumor-promoting function of MDSCs, we discovered CCAAT/enhancer binding protein alpha (C/EBPα) expression was significantly reduced in MDSCs from tumor-bearing mice compared to non-tumor-bearing hosts. Tumor-conditioned medium down-regulated C/EBPα expression, suggesting tumor secreted factors inhibiting the gene expression. Consistent with the function of C/EBPα in regulating the balance between proliferation and growth arrest in hematopoietic progenitors, myeloid lineage specific deletion of C/EBPα resulted in significantly enhanced MDSC proliferation and expansion, as well as an increase of myeloid progenitors and a decrease of mature cells. In addition, deletion of C/EBPα in MDSCs enhanced the pro-angiogenic, immune suppressive and pro-tumorigenic behavior of these cells by upregulating the production of iNOS and arginase, as well as MMP-9 and VEGF. Accordingly, tumors growing in C/EBPα conditional null mice displayed greater MDSC infiltration, increased vascularization and accelerated tumor growth. Taken together, this study reveals dual negative roles of C/EBPα in the expansion as well as pro-angiogenic and immune suppressive functions in MDSCs.